PENGGUNAAN TEKNIK TONGUE TWISTER UNTUK MENINGKATKAN PENGUCAPAN SISWA DI SMA NEGERI 4 KOTA TERNATE - Rini Heart; Anwar Ismail; Indry Widyasti Anwar (Cakrawala Bahasa, 2023)
The research aims to examine the effect of tongue twisters on students' pronunciation. The method used in this research is quantitative and the research design used is quasi-experimental. The sample in this study was tenth-grade students at SMA Negeri 4 Ternate City for the 2022/2023 academic year. They are from classes X2 and X5, class X2 is the experimental class and X5 is the control class. Each group consists of 10 students. The experimental group was taught using the tongue twister technique while the control group was taught using recount text. The method of data collection was done by using a test that is pretest and posttest. As for data analysis, the authors used the ELSA and SPSS applications version 25 to find out the results of the pretest and posttest. Based on calculations, the average pre-test score of the experimental class was 80 while the average post-test score of the control class was 64. The study’s results explained that the use of the tongue twister technique affected students' pronunciation abilities. This can be seen from the results of the independent samples test where students who were taught the tongue twister technique (experimental group) scored 0.000 where the hypothesis was that if the test result was lower than 0.05 then Ha was accepted and Ho was rejected. The test results show that the alternative hypothesis is accepted because the test value is 0.000 which is smaller than the significant value of 0.05. Based on the test results, it can be concluded that this technique can affect students' pronunciation. This shows that the use of tongue twisters is effective to be taught to students to improve students’ pronunciation skills.